2020
DOI: 10.1088/1361-6463/abc0c0
|View full text |Cite
|
Sign up to set email alerts
|

Competition of whispering gallery lasing modes in microwire with hexagonal cavity

Abstract: The competition characteristics of different orders of whispering-gallery lasing modes in a single ZnO microwire with hexagonal cavity are investigated comprehensively. As the scale of the cavity increases, the mode competition would be emerging strongly. The high-order whispering-gallery mode (WGM) lasing is indicated to be transverse electric modes with polarization dependence of about 86%. In addition, the competition of whispering-gallery lasing modes depends strongly on the diameter of cavities and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Further confirmation of lasing onset using narrowing of the full width at half maximum and annihilation of the Purcell-enhanced spontaneous emission is shown in Section III of the Supporting Information. 36,49 At 8000 μW pump power, the RGB lasers are well balanced, and the calculated chromaticity (0.297, 0.323) is very close to that of the CIE 1931 standard white illuminant D65 (0.312, 0.329), 50 as shown in Figure 3b. By further increasing the pump power to 8800 μW (0.296, 0.328), the CIE coordinate of the laser shifts little, as the RGB lasers are saturated.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Further confirmation of lasing onset using narrowing of the full width at half maximum and annihilation of the Purcell-enhanced spontaneous emission is shown in Section III of the Supporting Information. 36,49 At 8000 μW pump power, the RGB lasers are well balanced, and the calculated chromaticity (0.297, 0.323) is very close to that of the CIE 1931 standard white illuminant D65 (0.312, 0.329), 50 as shown in Figure 3b. By further increasing the pump power to 8800 μW (0.296, 0.328), the CIE coordinate of the laser shifts little, as the RGB lasers are saturated.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…The 53 μm-diameter microsphere cavity has abundant resonant modes in the visible band; therefore, the competition between the lasing modes and the spontaneous emission is very intensive. Further confirmation of lasing onset using narrowing of the full width at half maximum and annihilation of the Purcell-enhanced spontaneous emission is shown in Section III of the Supporting Information. , …”
Section: Resultsmentioning
confidence: 80%
“…On the other hand, the hexagonal prism‐like resonator could provide polarization selection mechanism for WGMs feedback emission, resulting in the final anisotropic lasing output. [ 34 , 35 , 36 , 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…Hence, GaN MWs naturally suit potential applications as optical resonators [8,9] for integrated lasers [10,11] and sensors [6,12]. Previous studies have shown how GaN nanostructures can be used for confinement of whispering gallery (WGM) and Fabry-Perot (FPM) modes [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, GaN MWs naturally suit potential applications as optical resonators [8,9] for integrated lasers [10,11] and sensors [6,12]. Previous studies have shown how GaN nanostructures can be used for confinement of whispering gallery (WGM) and Fabry-Perot (FPM) modes [13][14][15][16]. Optical resonators supporting WGM can be applied for cavity devices with exceptional properties such as small mode volume, high power density, and narrow spectral linewidth [12,17].…”
Section: Introductionmentioning
confidence: 99%